Gas metal arc welding - Davis, G.W; Lansdell, Jeff; Harrell, Billy (CEV Multimedia, 1990)
The presentation focuses on the step-by-step safety procedures involved in setup and operation of the Gas Metal Arc (GMA) welder. Proper clothing, safety and equipment are discussed. Twelve welds (including butt weld, lap weld, T-weld, lace fillet, and others) are performed in both flat and vertical positions. Each weld is accompanied by expert narration and followed by discussion. The adjustment of shield gas flow, voltage control and wire speed control are discussed. A supplement is included.